PERAN CITY BRANDING DAN EVENT PARIWISATA DALAM MENIGNKATKAN KUNJUNGAN WISATAWAN - Lailatus sa’diya; Nurita Andriani (Kompetensi (Competence : Journal of Management Studies), 2018)
ABSTRACT The natural and cultural wealth of the regions in Indonesia has become a tourism potential to be developed in improving the country's economy. The implementation of regional autonomy has encouraged the government to further develop and market the advantages of the tourism sector, one of which is creating city branding. City branding can attract the attention of tourists to visit an area because the city can build a clear identity, strong associations, and embed positive attributes so as to win competition with other cities, especially in the tourism sector. Tourism events as tourist attractions serve as one of the strengths of the local government and the community to attract visiting tourists. City branding and events can create perceptions for visitors so that they can stimulate the decision to visit tourists to an area.